2020
DOI: 10.1016/j.jaa.2020.101177
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure among the geometric earthworks of western Amazonia (Acre, Brazil)

Abstract: Inferring socio-political organisation among Amazonian geometric earthwork builders is a significant challenge.• Point process modelling is adapted for detecting multi-scalar spatial structure in a sample of geometric earthworks.• Controlling for first-and second-order spatial dependency highlights likely critical scale of spatial structure.• This information provides the first robust regional estimates of possible territorial integration.• Hierarchical (vertical) organisation is counter-indicated, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Indeed, southwestern Amazonia contains the earliest plant cultivation and domestication ( 9 , 35 ), the oldest anthropogenic soils ( 35 ), low-density urbanism ( 19 ), and now a much higher density of earthworks. The underlying spatial data distribution may offer valuable information about pre-Columbian practices before European contact ( 36 ).…”
Section: Modeling Basin-wide Distribution Of Earthworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, southwestern Amazonia contains the earliest plant cultivation and domestication ( 9 , 35 ), the oldest anthropogenic soils ( 35 ), low-density urbanism ( 19 ), and now a much higher density of earthworks. The underlying spatial data distribution may offer valuable information about pre-Columbian practices before European contact ( 36 ).…”
Section: Modeling Basin-wide Distribution Of Earthworkmentioning
confidence: 99%
“…These results confirm previous archaeobotanical and ethnobotanical data that have already shown that some species (e.g., B. excelsa , Astrocaryum spp., and Attalea spp.) are more abundant on and near archaeological sites across Amazonia ( 8 , 14 , 36 ). Species that are less frequent and abundant in areas with a higher probability of earthwork occurrence likely prefer habitats where earthworks are usually not found, such as sandy soils with lower fertility ( 7 ), or were disfavored by past practices that might have had detrimental effects on some species ( 45 ).…”
Section: Relationships With Domesticated Speciesmentioning
confidence: 99%
“…It demonstrated the analytical possibilities of using spatial statistics for non-systematic regional survey data. As verified in other regions, applying spatial statistical methods in correlation with environmental and cultural variables proved to be a valuable tool to understand regional patterns (Riris, 2020;Bevan et al, 2013), complementing previous site-based research in the region. The performed analysis proves the importance of comparing archaeological data to known environmental variables to explore their correlation on a large scale.…”
Section: Discussionmentioning
confidence: 85%
“…To study the spatial relationships of the Indigenous settlement patterns, we focused on applying Point Pattern Analysis, which is simply defined as the study of the spatial arrangement of points in space (Riris, 2020;Costanzo et al, 2021;Carrero-Pazos, Bevan and Lake, 2019). When the intensity of the point pattern is constant, i.e., corresponding to a stationary and isotropic process within the region, it is called a Homogeneous Poisson Process (HPP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation